Health Education : Stunting Prevention in Nagari Api-Api, West Sumatra - Fatimah Fatimah; Iswenti Novera; Yenni Elfira; Irwadi Irwadi; Ikhsan Amran; Leo Agustino (PT. Anagata Sembagi Education, 2024)
Nagari Api-Api Pasar Baru, Bayang, Pesisir Selatan, West Sumatra is one of the areas that still faces major challenges related to stunting. Stunting is characterized by impaired growth and development in children, caused by insufficient nutrition, frequent infections, and a lack of psychosocial stimulation. Globally, 149.2 million children under the age of five (22.0 percent) are affected by this condition. Based on the results of a national survey of stunting sufferers in Pesisir Selatan for the 2023 period, there were 2,314 cases, 29.8 percent of the total number of children in the area, or an increase of 4.6 percent compared to 2022 which was 25.2 percent. Of that number, only 470 cases were children from underprivileged families and the rest were from children from well-off families. In terms of age, 795 cases were children aged 0-24 months and 1,519 cases were aged 24-59 months.Preparation of Extension Materials and Media Preparation of Extension Preparation of extension materials that include information about stunting, characteristics, causes, impacts, and prevention methods. Schmidt stated that stunting is a condition of malnutrition that occurs over a long period of time, resulting in impaired height growth in children. This makes them shorter compared to the standard height for their age (Aryastami, 2017).The results of the counseling activity were that participants understood and understood the causes and how to prevent stunting in children.